INTERNATIONAL JOURNAL ON HUMANISTIC IDEOLOGY, VOL. V, NR. 1, SPRING-SUMMER 2012 - GLIGOR, Mihaela; TOTELECAN, Silviu G. (2012)
The International journal of Humanistic Ideology (IJHI) is a biannual scholarly journal devoted to the studies of humanities and social sciences, the nature and the origin of humanistic ideas. One of its primary aims is the integration of the results of the several disciplines so that its articles will have a synthetic character in order to acquaint the reader with the progress being made in the general area of socio-human studies. The articles of the journal are hosted by various international data bases, IJHI being regularly indexed and abstracted by CEEOL, EBSCO and ProQuest.